2022
DOI: 10.3389/fpsyg.2021.634911
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Sustainable Usage Intention of Mobile Payments: Extended Unified Theory of Acceptance and Use of Technology Model Combined With the Information System Success Model and Initial Trust Model

Abstract: Under the background of global cross-border mobile commerce (m-commerce) integration, the importance of cross-border payment research is becoming increasingly prominent and urgent. The important value of this study is to empirically research the influence power of key elements in using two different mobile payment (m-payment) platforms in Korea. The extended unified theory of acceptance and use of technology (UTAUT2) has been widely applied in various studies because of its strong interpretive power. In Korea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 102 publications
(159 reference statements)
6
26
0
Order By: Relevance
“…Second, this study proposed a more comprehensive integrated framework that was combined with ITM (Kim and Prabhakar, 2004 ) and UTAUT2 (Venkatesh et al, 2012 ) to confirm influencing factors that facilitated the initial trust, while examining the technology of the user terminal characteristics and the initial trust's influence on usage intention. According to the results of this research, it is concluded that the combined model provides a stronger interpretation on adoption willingness than UTAUT2 and ITM, separately, which is consistent with previous studies (Lin et al, 2019 , 2022 ; Lin and Wu, 2021 ; Lin X. C. et al, 2021 ; Lin X. et al, 2021 ). Compared with the single-model analysis, this two-dimensional combined framework can comprehensively confirm the factors that positively influence the usage intention of digital currency's technology.…”
Section: Discussionsupporting
confidence: 91%
“…Second, this study proposed a more comprehensive integrated framework that was combined with ITM (Kim and Prabhakar, 2004 ) and UTAUT2 (Venkatesh et al, 2012 ) to confirm influencing factors that facilitated the initial trust, while examining the technology of the user terminal characteristics and the initial trust's influence on usage intention. According to the results of this research, it is concluded that the combined model provides a stronger interpretation on adoption willingness than UTAUT2 and ITM, separately, which is consistent with previous studies (Lin et al, 2019 , 2022 ; Lin and Wu, 2021 ; Lin X. C. et al, 2021 ; Lin X. et al, 2021 ). Compared with the single-model analysis, this two-dimensional combined framework can comprehensively confirm the factors that positively influence the usage intention of digital currency's technology.…”
Section: Discussionsupporting
confidence: 91%
“…China, the US and Belgium). The UTAUT2 model has been an influential theoretical model for understanding the adoption of MPS (Lin et al, 2022;Migliore et al, 2022;Shin and Lee, 2021;Suo et al, 2022;Yuniarta and Purnamawati, 2021). However, we know little about the role of cultural factors in affecting the adoption of MPS.…”
Section: Country Differences In Mobile Payment Service 237mentioning
confidence: 99%
“…TAM, TRA and IDT) in predicting people's new technology use (Al-Saedi et al, 2019Albanna et al, 2022). In particular, the UTAUT2 model has been used by plenty of empirical studies examining the adoption of MPS (Lin et al, 2022;Migliore et al, 2022;Shin and Lee, 2021;Suo et al, 2022;Yuniarta and Purnamawati, 2021). In addition, the UTAUT2 model has been validated in several Asian, North American and European countries when predicting the adoption of MPS (Lin et al, 2022;Migliore et al, 2022;Suo et al, 2022).…”
Section: Literature Review 21 Mobile Payment Service (Mps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this paper chose UTAUT2 as an important theoretical basis. Regarding the literature on game use behavior and willingness, some scholars directly adopted UTAUT2 theory ( Ramírez-Correa et al, 2019 ; Harborth and Pape, 2020 ) but others modified, deleted, or supplemented research variables based on UTAUT2 to better apply them to specific research situations ( Jang and Byon, 2019 ; Baabdullah, 2020 ; Sharma et al, 2020 ; Lin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%